The Impact Of Service Innovation On Customer Satisfaction In Prodia Health - Christina Christina; Sri Hartini (Universitas Medan Area, 2020)
The era of Digital-Based Industry 4.0 has changed the company's strategic plans so that companies need to compete through increasing service innovation. To facilitate services for customers, Prodia Health Care creates a website and application to facilitate registration, payment, receipt of results and consultation where the current number of users is still low, so research is needed to analyze the factors that have an impact on Prodia customer satisfaction. The purpose of this study is to support service innovation towards customer satisfaction and improve the functional value and emotional value of Prodia Health Care customers. The path analysis method used as a method to study the influence and the big influence that occurs with a sample of 50 Prodia customers who have used digital services. The results of a positive and significant service innovation research on customer satisfaction, functional and emotional value have a positive and significant impact on customer satisfaction. However, the indirect orientation of functional value is not greater than service innovation. This, which results in a digital evaluation of Prodia's Health Care services, needs to be optimized to support increased customer satisfaction